The Influence of Social Media and Customer Trust on Decisions to Use Bridal Beauty Queen Services - Vanessa; Sri Rezeki (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine the Effect of Social Media and Customer Trust on the Decision to Use Bridal Beauty Queen Services. The research methodology used is quantitative descriptive method. The type of data used in this study is quantitative data, which is obtained in the form of numbers and numbers. Data sources are primary and secondary data. The population used is all customers who purchase services at Bridal Beauty Queen, totaling 78 people. From the population, selected with saturated sampling technique which means that the entire population becomes the research sample. The analysis method used is multiple linear regression with the regression equation User Decision = 4.547 + 0.559 Social Media + 0.201 Customer Trust. The results of the research analysis show that Social Media has a significant positive effect on Bridal Beauty Queen User Decisions and Customer Trust has a positive and significant effect on Bridal Beauty Queen User Decisions. Simultaneously Social Media and Customer Trust simultaneously have a significant and significant effect on the User Decision of Bridal Beauty Queen Services with the Adjusted R Square result of 0.672. This shows that 67.2% of the Bridal Beauty Queen Service User Decision is influenced by the Social Media and Customer Trust variables while the remaining 32.8% is influenced by other variables not examined in this study